Effect of Neuromuscular Training Program on Quality of Life After COVID-19 Lockdown Among Young Healthy Participants: A Randomized Controlled Trial - Marinkovic, Dragan; Macak, Drazenka; Madic, Dejan M.; Sporis, Goran; Kuvacic, Dalija; Jasic, Dajana; Petric, Vilko; Spehnjak, Marijan; Projovic, Aleksandra; Gojkovic, Zoran (Frontiers in Psychology, 2022)
Research in the period of COVID-19 lockdown and the effect of different exercise training programs on the quality of life (QoL) dimension is limited. This randomized control study as a part of which the impact of an eight-week neuromuscular training program on the 90 healthy young individuals’ QoL after COVID-19 lockdown were assessed using a short form of the WHOQOL-BREF questionnaire comprising of four domains (physical health, psychological health, social relations, and the environment). The intervention group (NT, n = 47) took part in a neuromuscular training program consisting of dynamic neuromuscular stabilization and whole-body vibration training. In contrast, the control group (CG, n = 43) did not participate in any programmed physical activity. From pre- to post-intervention test, the NT group significantly and substantially improved (mean change [95%CI]) all QoL domains, Physical for 12.78 scores [8.89, 16.64], Psychological for 13.12 scores [9.51, 16.74], Social Relationships for 20.57 scores [16.12, 25.02], and Environmental for 24.40 scores [21.45, 27.35]. These results suggest that the NT program could enhance QoL in young and healthy participants following a COVID-19 lockdown.